Book Review: Zlygostev V.A. Geroi “Sokrovennogo skazaniya” [Heroes of the “Secret History”] - Antonov I.V. (Золотоордынское обозрение)
Research objectives: This article analyzes a new book by independent historian, Valery Zlygostev, written in the historical, biographical genre. The book is dedicated to outstanding figures in the medieval history of the Mongols, their allies, and opponents, as have been preserved in written sources. It discusses the territories eventually covered by the Mongol Empire, stretching from the Mediterranean Sea to the Pacific Ocean, during the period from the eighth to thirteenth century. Zlygostev traced the process of the establishment of Mongolian statehood, the formation of the Mongol Empire, and the expansion of its borders until the end of the era of conquests in the 1270s. The author reconstructs the biographies of all the characters of this period on the basis of the Mongol chronicle of c. 1240, traditionally called the “Secret History,” alongside other sources. The scholarly novelty of the research lies in the presentation of the secondary and tertiary heroes of Mongolian history and their role in various military and political events that culminated in the creation of the greatest world empire in history. Particular attention is paid to the so-called “dark” period in the history of the Mongols stretching until the middle of the twelfth century, that is, the period of Chinggis Khan’s birth. This period is still insufficiently analyzed in historiography and yet is very important for clarifying the prerequisite conditions which brought about the subsequent unification of Mongolia and the conquests of Chinggis Khan and his successors in Asia and Europe. The author has done a tremendous job of analyzing all available sources and identifying all possible details of the biography of certain heroes. The book is recommended for everyone interested in the medieval history of Eurasia.